Pengaruh Pengungkapan Tanggung Jawab Sosial dan Tata Kelola Perusahaan Terhadap Kinerja Keuangan - Shyaila Anisa De Lavanda; Carmel Meiden (Universitas Muhammadiyah Jakarta, 2022)
The Covid-19 pandemic has regressed companies’ financial performance affecting the perspective of public and investors on sustainability that of the risk of financial distress. Companies need specific programs to improve this condition. Corporate Social Responsibility Disclosure (CSRD) and Good Corporate Governance (GCG) implementation are able to develop financial performance. This study aims to take a quantitative perspective to explore how CSRD and GCG affect financial performance. From high profile companies listed on the Indonesia Stock Exchange for the period 2018-2020, this study collects the sample using a non-probability technique and judgement method. The results show that CSRD, independent board of commissioners, audit committee, and firm size have significant effect on financial performance, while institutional ownership and board of directors have no significant effect on financial performance.